EFFECTS OF DIFFERENT SALINITY LEVELS ON ERYTHROCYTE COUNT, LEUKOCYTE COUNT, AND BLOOD GLUCOSE OF STRIPED CATFISH (Pangasianodon hypophthalmus) - M Riswan; Henni Syawal; Usman M Tang; Irwan Effendi; Ronal Kurniawan; Nur Ikhlas Syuhada; Rianti Putri; Sri Wahyuni; Asri Mursawal (Asian Journal of Aquatic Sciences, 2026)
Pangasianodon hypophthalmus is a stenohaline freshwater catfish that is increasingly exposed to salinity fluctuations due to tidal intrusion and the expansion of brackish water aquaculture. This study aimed to analyze the erythrocyte and leukocyte counts, as well as blood glucose levels, in P. hypophthalmus reared at different salinities. This study used a completely randomized design (CRD) with four treatments: 0 ppt salinity, 5 ppt salinity, 7 ppt salinity, and 9 ppt salinity, with three replicates. The hematological parameters analyzed included total erythrocytes, total leukocytes, and blood glucose. The results showed that salinity had a significant effect (p < 0.05) on total erythrocytes, total leukocytes, and blood glucose. A salinity of 5 ppt produced an optimal hematological profile, with a total erythrocyte count of 2.25 × 10⁶ cells/mm³, a total leukocyte count of 7.65 × 10⁴ cells/mm³, and blood glucose of 52.33 mg/dL. These findings indicate that a salinity of 5 ppt is the optimal salinity threshold for P. hypophthalmus aquaculture in brackish water environments and provide a physiological basis for adaptive aquaculture management amid changing environmental conditions